Faktor-Faktor Yang Menentukan Perilaku Konsumen Dalam Mengadopsi Teknologi Informasi - Ronny Ronny (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2014)
The study about individual behavior in the adoption of information technology has already performed in any kinds of research with the different of brand and type of product, different location, and the different individual and organization. This scientific article analysis factors determine the adoption of information technology of the various research in Indonesia and foreign country with the limitation on the adoption of information technology by the individual. The main focus of the analysis in on the consumer behavior at the time of performing the buying process and at the time of using the product. The result of analysis shows that the four variables influenced the individual in adopting the information technology are economic, educational, social influence, and benefit, as well as the easy of using technology.